'Deal with It. Name It': the diagnostic moment in film. Issue 3 (14th March 2017) - Jutel, Thierry; Jutel, Annemarie
Abstract : The moment a serious diagnosis is announced creates an important crisis for a patient, as it shifts their sense of self and of their future potential. This essay discusses the creative representation and use of this diagnostic moment in film narratives. Using Still Alice, A Late Quartet, Wit and Cléo from 5 to 7 as examples, we describe how each of these uses the diagnostic moment in relation to narrative construction and characterisation in recognisable ways. We associate the diagnostic moment with certain narrative and visual devices that are frequently implemented in films as means for character development, and for managing the audience's empathy. This is the case whether or not the diagnosis is contested or accepted, and whether the diagnostic moment is the frame for the narrative, or a closing device. By analysing its representation in film, we emphasise the cultural significance of diagnosis as a life-transforming event.